Study on Flow Boiling Characteristics in Rectangle Channel After Formation of Blisters - Huang, Huijian; Chen, Chong; Liu, Luguo; Liu, Yu; Li, Linfeng; Yu, Hao; Wang, Mingjun; Qiu, Suizheng (Frontiers in Energy Research, 2021)
Abstract: Plate-type fuel elements is one of the first fuel structure choice for the novel integrated pressurized water reactor, however, blisters will be formed on the cladding under irradiation and fission. In this work CFD method was used to investigate the subcooled boiling characteristic of the rectangle channel with rould and pillow blisters and the modified RPI model was also been proposed, we can draw the conclusions as follows: For the channel with round blister, the blisters will increase the local flow resistance and more fluid will flow through center of the channel. Boiling occurred only in the area near the edges, no boiling occurred at the center of the channel .The boiling region of pillow-blisters is wider and concentrated in the region between two pillow blisters and the downstream of the non-blisters side. The dry out area for channel with pillow-blisters and round blisters are both in the downstream region of blisters.